Analisa Kinerja Pada Perencanaan TD-LTE ADVANCED Studi Kasus Kota Bandung - Purusadi Hastruman; Arfianto Fahmi; Uke Kurniawan Usman (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
In LTE Advanced technology there are two methods used in the duplexing process, there are frequency division duplex (FDD) wherein this duplexing concept communication is divided based on the frequency and the other is time division duplex (TDD) where communication is divided based on the time. Duplexing using the TDD method has advantages of handling data-based services that the majority have Non-Guarantee Bit Rate (N-GBR) characteristics because most of these services do not require a minimum bit rate to be able to work and this is an advantages because nowadays people like to use data-based services. So in this LTE Advanced network planning using the TDD method,  frequency 2300 MHz for TD-LTE advanced, and parameters that to be the main focus are throughputs, reference signal received power (RSRP), reference signal strength indicator (RSSI), carrier to interference noise ratio (CINR), and block error rate (BLER). And the result of the simulations from TD-LTE Advanced planning are the mean of throughput value is 3,5 Mbps, mean of RSRP value is -110,8 dBm, mean of RSSI value is -72,36 dBm, mean of CINR value is 4,81 dB, and mean of BLER value is 0,07%.